Beyond Alzheimer's disease: Can bilingualism be a more generalized protective factor in neurodegeneration?. (October 2020) - Voits, Toms; Pliatsikas, Christos; Robson, Holly; Rothman, Jason
Abstract: Bilingualism has been argued to have an impact on cognition and brain structure. Effects have been reported across the lifespan: from healthy children to ageing adults, including clinical (ageing) populations. It has been argued that active bilingualism may significantly contribute to the delaying of the expression of Alzheimer's disease symptoms. If bilingualism plays an ameliorative role against the expression of neurodegeneration in dementia, it is possible that it could have similar effects for other neurodegenerative disorders, including Multiple Sclerosis, Parkinson's and Huntington's Diseases. To date, however, direct relevant evidence remains limited, not least because the necessary scientific motivations for investigating this with greater depth have not yet been fully articulated. Herein, we provide a roadmap that reviews the relevant literatures, highlighting potential links across neurodegenerative disorders and bilingualism more generally. Highlights: Bilingualism contributes to brain reserve in ageing. Bilinguals show delayed onset of Alzheimer's Disease symptoms. Limited research directly testing effects on types of clinical neurodegeneration. Brain and behaviour links across other clinical neurodegeneration and bilingualism. Bilingualism outcomes in other types of neurodegeneration is an empirical question.